Akar Konflik Pertambangan Emas di Gunung Tumpang Pitu Banyuwangi - Setiawan, Eko (Prodi Sosiologi FISIP ULM, 2024)
The existence of a gold mine at Mount Tumpang Pitu is a valuable asset for Indonesia, but it faces a negative stigma due to its environmental impacts, including landscape destruction, landslides, and water pollution, leading to conflicts between local communities, companies, and the government. This research aims to analyse the roots of conflict between local communities and mining companies, the impacts of mining, and alternative conflict resolution that can be implemented. The research method used is a literature study, with data collection from books, magazines, reports, and journals related to mining conflicts. The results show that community dissatisfaction with the Banyuwangi Regent's approval of the mining permit, which is considered legally flawed, as well as the negative impacts on the environment and livelihoods, has resulted in divisions among the community and mobilisation of protests. It was also found that the company's approach of prioritising economic profit over ecological and social sustainability contributed to the prolonged conflict. Therefore, government involvement in protecting community rights and monitoring mining activities in line with sustainable development is crucial. Mediation involving neutral third parties and the establishment of special institutions to handle conflicts are also needed to achieve constructive dialogue. This research is expected to provide theoretical insights in understanding mining-related social conflicts and practical benefits for policy makers in formulating more sustainable and inclusive mining policies.